2009
DOI: 10.3892/or_00000519
|View full text |Cite
|
Sign up to set email alerts
|

Clues pointing to simple hysterectomy to treat early-stage cervical cancer

Abstract: Abstract. Radical hysterectomy and pelvic lymphadenectomy is recommended for stage Ia2-Ib1 cervical cancer while parametrial involvement (PI) is rare. Our aim was to evaluate criteria to select women with low risk of PI that could benefit from simple hysterectomy. Factors associated with low risk of PI were analyzed in a series of 37 patients with stage Ia2-Ib1 cervical cancer undergoing radical hysterectomy and sentinel lymph node procedure from 2003 to 2008. PI was associated with tumor size (p<0.001) and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…46,47 In low risk cases, simple hysterectomy or trachelectomy, with either pelvic lymphadenectomy or sentinel lymph node assessment, may be adequate surgical treatment. 48,49 When the patient desires fertility, she may be offered a choice of the following: hysterectomy may be considered in these cases. Pelvic lymphadenectomy should always be included on account of the high frequency of lymph node involvement.…”
Section: Stage Ia2mentioning
confidence: 99%
“…46,47 In low risk cases, simple hysterectomy or trachelectomy, with either pelvic lymphadenectomy or sentinel lymph node assessment, may be adequate surgical treatment. 48,49 When the patient desires fertility, she may be offered a choice of the following: hysterectomy may be considered in these cases. Pelvic lymphadenectomy should always be included on account of the high frequency of lymph node involvement.…”
Section: Stage Ia2mentioning
confidence: 99%
“…[46][47][48] In low-risk cases (no LVSI, sentinel node negative), simple hysterectomy or trachelectomy, combined with either pelvic lymphadenectomy or sentinel lymph node (SLN) assessment, may be adequate surgical treatment. 49,50 When the patient desires fertility, she may be offered a choice of the following: (1) cervical conization with pelvic lymphadenectomy (open or minimally invasive surgery [MIS]); or (2) radical trachelectomy with pelvic lymphadenectomy by abdominal, vaginal, or MIS route. 51,52 Post-treatment follow-up After fertility sparing surgery, follow-up with 3-monthly Pap smears for 2 years, then 6-monthly for the next 3 years is recommended.…”
Section: Stage Ia2mentioning
confidence: 99%
“…Second, the use of SCC as a tumor marker in a population containing nonsquamous cell cancers may be controversial. Benoit et al proposed a nomogram to predict the PI in the early-stage CC ( 13 ). In this study, sentinel lymph node, tumor size, DSI, and LVSI were included.…”
Section: Discussionmentioning
confidence: 99%
“…Different from their nomogram model, this study found that VI played a key role in the occurrence of the PI, which was proved by the Cox regression analysis. A study by Coutant et al reported that three of six patients with the PI and three of 31 patients without the PI had vaginal involvement ( p = 0.04) ( 13 ). It is known that the occurrence of the PI is associated with the rate of tumor spread to the vaginal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation